Husavik Energy - Multiples Use of Geothermal Energy - Hjartarson, Hreinn (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2005)
Húsavík is the largest town in Northeast Iceland with a population of around 2,500 inhabitants. Húsavík has been an active trading post since 1614 and the town’s economy has since that time mainly been based on fishing, fish processing and service for the surrounding countryside. However, tourism and other industries have played an increasing role during recent years. The main natural resources of the Húsavík area are plentiful fishing waters, geothermal heat and an abundant supply of fresh, cold water